Mulheres na reforma agrária e políticas de crédito: avaliação do Pronaf Mulher em assentamentos de Monsenhor Tabosa-CE - Duarte, Ana Maria Timbó (2010)
This research sought to evaluate the Programa Nacional de Fortalecimento da Agricultura Familiar, titled PRONAF-Mulher, as regards the capacity to generate jobs and income for women in agrarian reform in two settlements in the city of Monsenhor Tabosa. This ex-post evaluation research is exploratory, with quantitative and qualitative approach, being empirical and inspired in some principles of the triangulation of methods. In the survey for secondary data, it was used the theoretical research (bibliographic and documental). The survey for primary data was conducted through applying questionnaires to the beneficiaries of the program and also through interviews with the main individuals involved. The paper briefly describes the historic of the Brazilian agrarian question, focusing on the family farm and rural women. With regard to the ability of offering employment and income for women in agrarian reform, the research indicated that PRONAF-Mulher alone was not able to promote this goal, however, if there are changes, it may be an indispensable tool in this achievement. The results demonstrated that there are potentialities and limits of PRONAF-Mulher.